Pemberian Bimbingan Pribadi Sosial terhadap Narapidana Lanjut Usia sebagai Upaya Peningkatan Kualitas Hidup - Rama Fatahillah Yulianto (Jurnal Ilmiah Penegakan Hukum, 2021)
Prisoners are the designation for people or citizens who commit criminal acts and have followed all procedures of the criminal justice system or the Integrated Criminal Justice System in Indonesia and have obtained permanent legal force or inkracht. The state through the Correctional Institution (Lapas) is obliged to carry out guidance and provide rights, because in fact it is only the right to freedom of movement. The research method used in this study is to explain empirical research that focuses on the behavior of the legal community, and this research requires primary data as the main data in addition to secondary data. This research is a type of field research with a qualitative approach. The main techniques in collecting data are observation, and interviews conducted at the Jember Class IIA Penitentiary. The results of the study indicate that the social condition of the elderly must be considered, because of their psychological or mental condition when facing stressful situations. The provision of personal social guidance is very appropriate to improve the quality of life after being fostered and in prison. Guidance is an effort to help individuals, especially the elderly, so that they can develop their competencies